Polymer optical fiber for in-shoe monitoring of ground reaction forces during the gait - Leal-Junior, A. G.; Frizera, A.; Avellar, L. M.; Marques, C.; Pontes, M. J. (IEEE Sensors Journal, 2018)
Ground reaction force (GRF) measurement is usually made by means of force platforms, which can lead to errors when the foot is not precisely placed inside the platform boundaries. Although electronic in-shoe plantar pressure sensors solve this problem, they lack in stability, robustness to impact loads and also can present some errors and inconsistencies. Polymer optical fibers (POF) present high elastic strain limits, fracture toughness, flexibility in bend, and relative low cost and are not influenced by electromagnetic fields, which enable their application for in-shoe plantar pressure measurements. This paper presents an in-shoe system to measure the vertical GRF during the gait cycle. The system comprises of four POF sensors in an insole. Since the polymer does not have a constant response with stress or strain due to its viscoelasticity, a compensation technique for this effect is also proposed. The proposed insole is compared with a commercial force platform, and a root mean squared error of 5.30 N was obtained. Results also show the feasibility of the system to measure the GRF during the gait and the identification of all subdivisions of the stance phase with the additional advantages of full portability, lower cost, and higher flexibility than the one presented by commercial force platforms and fiber Bragg gratings-based insoles.